2022
DOI: 10.31797/vetbio.1173455
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of antifungal activity mechanisms of alpha-pinene, eugenol, and limonene

Abstract: Plant essential oils are preferred in cosmetics, medicine, food, and beverage industries for various purposes. α-Pinene is found mainly in eucalyptus oils, eugenol is the active ingredient in clove oil, and limonene is the major component in the oil of citrus fruit peels. In this study, we aimed to determine the antifungal activity of α-pinene, eugenol, and limonene against Saccharomyces cerevisiae yeast cells. Besides, we focused on revealing the target side of the compounds on the yeast cells. Firstly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The proven effectiveness of the compound α-pinene as an antifungal agent is widely attributed to its mode of action targeting fungal yeasts. Studies have indicated that this compound interacts significantly with the cell membrane, resulting in its rapid destabilization and subsequent rupture, leading to the leakage of intracellular content [46]. This phenomenon has been observed in fungal species of both Candida spp.…”
Section: Discussionmentioning
confidence: 94%
“…The proven effectiveness of the compound α-pinene as an antifungal agent is widely attributed to its mode of action targeting fungal yeasts. Studies have indicated that this compound interacts significantly with the cell membrane, resulting in its rapid destabilization and subsequent rupture, leading to the leakage of intracellular content [46]. This phenomenon has been observed in fungal species of both Candida spp.…”
Section: Discussionmentioning
confidence: 94%